A Rare Case of Thyroid Metastasis from Pancreatic Adenocarcinoma - Kelly, Michael E; Kinsella, John; d’Adhemar, Charles; Swan, Niall; Ridgway, Paul F (JOP. Journal of the Pancreas, 2011)
Context Thyroid metastasis from pancreatic adenocarcinoma is extremely rare, with only two previous cases in the literature. We report a case of pancreatic adenocarcinoma metastasising to the thyroid. We review the incidence, diagnosis, and management of this rare occurrence. Case report A 38-year-old man with a synchronous 6-month history of thyroid swelling, presented with epigastric pain and signs of obstructive jaundice. He was investigated by abdominal computerised tomography and endoscopic retrograde cholangiopancreatography. The diagnosis of pancreatic neoplasm was made. His thyroid neoplasm was investigated at another tertiary centre and thought to be a papillary neoplasm. He underwent a pancreaticoduodenectomy and recovered well post-operatively. Eight weeks later he had a total thyroidectomy. Histology confirmed that the thyroid mass was both morphologically and immunophenotypically similar to the pancreatic neoplasm. Conclusion This case demonstrates the importance of a full investigation when a patient with suspected neoplastic history presents with a thyroid nodule. We outline the crucial role that immunohistochemistry plays in detecting and classifying primary and secondary thyroid neoplasms. The detection of a solitary thyroid metastasis from pancreatic adenocarcinoma may indicate a poor prognosis, and it is debatable whether resection of the primary should be undertaken when it presents with a solitary metastasis. Image: Logo of the Adelaide and Meath Hospital, Dublin Incorporating the National Children’s Hospital. Dublin, Ireland.